2022
DOI: 10.5114/pjr.2022.117968
|View full text |Cite
|
Sign up to set email alerts
|

Can epicardial and pericardial adipose tissue volume predict the presence and severity of coronary artery disease?

Abstract: Purpose Excessive accumulation of free fatty acids in the coronary arteries can lead to coronary artery disease (CAD). Quantification of epicardial adipose tissue (EAT) and pericardial adipose tissue (PAT) is beneficial to understand its relationship with CAD, hypertension (HT), and diabetes. Material and methods This retrospective study included 54 patients who underwent CT coronary angiogram using a multidetector row CT scanner. The EAT and PAT volumes from cardiac im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 26 publications
0
4
1
Order By: Relevance
“…An explanation could be the composition of our patient population that might have had an influence on regression analysis for Agatston score and CAD-RADS score. The distribution of gender -a larger male population -and the number of patients with diabetes -a less diabetic population in our study -are pre viously found influencing factors of Agatston score and differ substantially from the study of Panda et al [14,[20][21][22]. Most likely reason is that the mean Agatston score in our population is about half that found in the compared study by Panda et al As discovered by Mahabadi et al the association of epicardial fat volume on the progression of coronary calcification is more emphasised in subjects with low body mass index and decreases with the degree of adiposity [23].…”
Section: Discussioncontrasting
confidence: 97%
See 4 more Smart Citations
“…An explanation could be the composition of our patient population that might have had an influence on regression analysis for Agatston score and CAD-RADS score. The distribution of gender -a larger male population -and the number of patients with diabetes -a less diabetic population in our study -are pre viously found influencing factors of Agatston score and differ substantially from the study of Panda et al [14,[20][21][22]. Most likely reason is that the mean Agatston score in our population is about half that found in the compared study by Panda et al As discovered by Mahabadi et al the association of epicardial fat volume on the progression of coronary calcification is more emphasised in subjects with low body mass index and decreases with the degree of adiposity [23].…”
Section: Discussioncontrasting
confidence: 97%
“…Recently, epicardial fat volume has been studied with contradictory data: On the one hand, Panda et al . found a positive correlation between epicardial fat volume and Agatston score [ 14 ]. This was not the case in our collective of 96 patients, which nearly doubles the patient number in the mentioned study ( n = 54) but is still a relatively small patient population.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations